The Usage of Object Oriented Approach in Software Development Companies - Vikneswary, Anne (2003)
Object orientation (00) has become a new buzzword for computer applications. Things are touted as being object oriented, with the implication that this is the "new" and "better" way to do things. As there are many approaches used to develop systems, therefore the software industry has to cope with the rapid technological evolution and the global market competition, in order to satisfy the growing user demands for quality, services and bandwidth. This project seeks a review of the status of the object-oriented approach among the software industry. Based on this, I will analyze the awareness of the object-oriented approach among software developers. In addition to this, the level of usage of the object-oriented approach in software development activities will also be examined. The results obtained will be statistically analyzed using SPSS (Statistical Package for Social Sciences), and discussed later in the light of the literature reviewed